1997
DOI: 10.1063/1.119065
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-scale Si selective epitaxial growth on Si(001) surfaces using the thermal decomposition of ultrathin oxide films

Abstract: Reduction of sidewall defect induced leakage currents by the use of nitrided field oxides in silicon selective epitaxial growth isolation for advanced ultralarge scale integration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…After oxygen exposure, the ͑2 3 1͒ reflection high-energy electron diffraction (RHEED) pattern disappeared and only ͑1 3 1͒ spots from the substrate remained. Also, in our previous scanning tunneling microscopy study, no ordered structure was recognized on the surface [16]. Note that the contrast of the initial ͑1 3 2͒ and ͑2 3 1͒ terraces was reversed in each oxidation step, 0031-9007͞98͞80(2)͞345(4)$15.00…”
mentioning
confidence: 94%
“…After oxygen exposure, the ͑2 3 1͒ reflection high-energy electron diffraction (RHEED) pattern disappeared and only ͑1 3 1͒ spots from the substrate remained. Also, in our previous scanning tunneling microscopy study, no ordered structure was recognized on the surface [16]. Note that the contrast of the initial ͑1 3 2͒ and ͑2 3 1͒ terraces was reversed in each oxidation step, 0031-9007͞98͞80(2)͞345(4)$15.00…”
mentioning
confidence: 94%
“…[2][3][4]9 Recently, we have shown that the formation and extension of voids can be observed dynamically by high-temperature scanning tunneling microscopy ͑STM͒. 10,11 These studies revealed that surface roughening during void formation is caused by the etching of void bottoms which supplies the Si atoms necessary for the oxide decomposition. A typical void depth is 0.3-0.5 nm when the oxide thickness is 0.3 nm, but the surface shows pronounced roughness when oxide layers are about 1 nm thick.…”
Section: Introductionmentioning
confidence: 99%
“…The oxide thickness was estimated from Si 2 p corelevel spectra. 12 As we previously reported, even though SiO 2 films are a typical insulator, stable STM images of the oxide surface can be acquired by increasing the sample bias to ϩ5 V. 9,10,12 In this study, we used a Pt-Ir tip and all STM images were obtained at a ϩ5 V sample bias with a 0.5 nA constant tunneling current. Figure 1 shows an STM image of a 1-nm-thick SiO 2 film grown on a Si͑111͒ substrate.…”
mentioning
confidence: 99%